ANALISIS PENGUKURAN KINERJA PERUSAHAAN MENGGUNAKAN METODE BALANCED SCORECARD PADA APOTEK KASIH FARMA - Aprisa Rian Histiarini; Sanny Hahury; Sedrianus Mangalik (Universitas Muhammadiyah Sorong, 2022)
Balanced scorecard (BSC) is an alternative performance measurement that aims to combine financial and non-financial performance measures. This measurement is the result of a process based on the mission and strategy of a company. There are four aspects that are measured in the balanced scorecard (BSC), namely financial perspective, customer and consumer perspective, internal business process perspective and growth and learning perspective. The result of this research is that the company's performance from a financial perspective produces poor performance results. Compared to the company's standards, the performance is just as bad. From the perspective of internal business processes, it shows that the company's performance is getting better. Based on the measurements made, the researcher concludes that the company's performance in the learning and growth perspective shows better results. This study aims to analyze the activity ratio at the Kasih Farma Pharmacy. The data used are primary data and secondary data, the data obtained through interviews and documentation. The research population is the financial statements as a whole and the sample is the 2019-2020 financial statements. The data analysis technique uses financial ratios , namely the activity ratio consisting of inventory turnover, ROI and Profit Margin. The results showed from 2019-2020 that the inventory turnover was 3.03 times, 1.93 times, and 0.93 times, in this case the financial performance was classified as poor.